Student Perceptions of Skills Training Program as a Mean of Preparation for Nurse Profession Program - Erma Wahyu Mashfufa; Lilis Setyowati (STIKes Patria Husada Blitar, 2022)
The nursing profession must be pursued through higher education. Practice vehicles, such as hospitals require students to pass a skills test before they can practice. The Nursing Study Program, FIKES UMM, has implemented a matriculation program for students who will join the Nursing Profession. This activity has been carried out for a long time and has undergone several method changes to produce more effective outputs. However, there has never been an evaluation of how successful and valuable this program is for students. This type of research is a descriptive study because the researcher only observed Student' Perceptions Skills Training Programs in Preparing to Participate in Nursing Professional Education. The population in this study were all students of professional practice Nurses wave 20, a total of 50 respondents were taken by total sampling technique. The Dundee Ready Education Environment Measure (DREEM) questionnaire is appropriate for measuring the learning environment. Data analysis was carried out descriptively with percentages, tables, mean, and standard deviation.Â The result has shown that a score the DREEM questionnaireÂ 200 value indicates that there is a positive perception of the matriculation learning environment that has been carried out in preparation for entering professional practice, including the expertise of the teacher/facilitator.Â Students' perceptions of the matriculation program for the preparation of professional education are positive. On the other hand, to improve student skills to be more optimal, it is necessary to enhance the skills of facilitators and more supportive facilities and infrastructure